2012
DOI: 10.1007/978-3-7091-0932-8_25
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Dysfunction in Alzheimer’s Disease

Abstract: Generation of amyloid peptide (Aβ) is at the beginning of a cascade that leads to Alzheimer's disease (AD). Amyloid precursor protein (APP), as well as β- and γ-secretases, is the principal player involved in Aβ production, while α-secretase cleavage on APP prevents Aβ deposition. Recent studies suggested that soluble assembly states of Aβ peptides can cause cognitive problems by disrupting synaptic function in the absence of significant neurodegeneration. Therefore, current research investigates the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 179 publications
3
61
0
Order By: Relevance
“…Synapse formation and plasticity are necessary for memory recall and consolidation. Previous studies have revealed that synapse loss is associated with cognitive impairment observed in various cognitive dysfunction models, including AD (24,25), middle cerebral artery occlusion (26) and 2VO (27). In the present study, BHD treatment evidently alleviated the synaptic loss induced by cerebral hypoperfusion.…”
Section: A B C Dsupporting
confidence: 65%
“…Synapse formation and plasticity are necessary for memory recall and consolidation. Previous studies have revealed that synapse loss is associated with cognitive impairment observed in various cognitive dysfunction models, including AD (24,25), middle cerebral artery occlusion (26) and 2VO (27). In the present study, BHD treatment evidently alleviated the synaptic loss induced by cerebral hypoperfusion.…”
Section: A B C Dsupporting
confidence: 65%
“…The neurodegeneration observed in AD has been associated with progressive decrease in neuronal activity and synaptic dismantling91039. Modulation of intrinsic properties of individual neurons represents a potential strategy for preventing and/or halting AD progression.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing attention has been given to the possibility that synaptic dysfunction within neural networks is an early, initiating event of disease pathogenesis possibly leading to neuronal death (Caviness, 2014; Li et al, 2003; Marcello et al, 2012; Palop and Mucke, 2010). For instance, alterations of basal ganglia circuitry that lead to deficits in motor control and cognitive processes precede loss of substantia nigra neurons in PD (Meredith and Kang, 2006; Muller et al, 2013) and striatal spiny neurons in HD (Mazarakis et al, 2005; Milnerwood and Raymond, 2007; Usdin et al, 1999), respectively.…”
Section: Introductionmentioning
confidence: 99%